Medicaid Family Planning Waivers in 3 States - E. Kathleen Adams PhD; Katya Galactionova MA; Genevieve M. Kenney PhD (SAGE Publishing, 2015)
Effects of Medicaid family planning waivers on unintended births and contraceptive use postpartum were examined in Illinois, New York, and Oregon using the Pregnancy Risk Assessment Monitoring System. Estimates for women who would be Medicaid eligible "if" pregnant in the waiver states and states without expansions were derived using a difference-in-differences approach. Waivers in New York and Illinois were associated with almost a 5.0 percentage point reduction in unwanted births among adults and with a 7 to 8.0 percentage point reduction, among youth less than 21 years of age. Oregon's waiver was associated with an almost 13 percentage point reduction in unintended, mostly mistimed, births. No statistically significant effects were found on contraceptive use.